Dot cards application development to improve counting ability 1-10 students with medium intellectual disability - Asri Dwi Puspasari; Sunardi Sunardi; Subagya Subagya (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
The concept of counting in this research is the sum of the numbers 1 to 10. Based on the results of the observations, it was found that the low counting ability of student with medium intellectual disability in class XI was due to limited media to support the learning process. Learning to count for student with medium intellectual disability should use concrete and interesting media. The purpose of this research was to produce learning media, namely a dot cards application to improve the numeracy skills of student with medium intellectual disability. The method is a research and development that adopts Borg and Gall with data analysis techniques using descriptive statistic. The results of data analysis from the validator's assessment and product trials get results in the verry good category. Based on the results of this analysis, it can be stated that the application dot card product is feasible and can be used to increase the counting ability of 1-10 student with medium intellectual disability.